PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN GOOGLE SITES PADA MATERI ENERGI DAN SUMBER ENERGI DALAM KEHIDUPAN SEHARI-HARI DI KELAS IV SDN 05 INDRALAYA - Sari, Indah; Maharani, Siti Dewi; Adikara, Fahmi Surya (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to develop an Interactive Learning Media assisted by Google Sites for the topic of Energy and Energy Sources in Everyday Life for Grade IV students at SDN 05 Indralaya. The type of research used is Research and Development (R&D), employing the ADDIE development model, which in this study includes only four stages: Analysis, Design, Development, and Implementation. The subjects of this study were 18 fourth-grade students from class IV C at SDN 05 Indralaya. The result of the research is a learning media product supported by Google Sites. Based on the media validation results assessed by validators, the total score for media aspects from the media expert was 90%, categorized as “Highly Valid.” The material expert gave a score of 93.75%, also categorized as “Highly Valid,” and the practitioner expert gave a score of 94.64%, also categorized as “Highly Valid.” Student responses after small-group and large-group product trials with 18 fourth-grade students at SDN 05 Indralaya showed scores of 95% for the small group and 97.22% for the large group, both categorized as “Very Attractive.” Based on these assessments, it can be concluded that the interactive learning media assisted by Google Sites is highly valid and feasible to be used as a learning medium in the teaching and learning process at school.